OP0070 ONSET TO DIAGNOSIS TIME PREDICTS SURVIVAL RATE IN TAKAYASU ARTERITIS - Popov, A.; Borodina, I.; Shardina, L. (Annals of the rheumatic diseases, 2021)
Takayasu arteritis (TA) is large vessel vasculitis. In spite of relatively high 5 to 15 years survival rate, TA affects young persons and causes major cardiovascular events, disability and preterm deaths [1]. Nowadays, though new high-resolution visualization and effective treatment options are available, quite a large number of TA patients remain undiagnosed and untreated for years [2]. To assess the influence of timely TA diagnosis and treatment initiation on the survival rate and cardiovascular events risk. A retrospective cohort study included 183 patients (139 females, 44 males), enrolled during the period from 1979 to 2018 after TA diagnosis verification according to ACR1990 criteria [3]. All subjects have been followed up at the Sverdlovsk Regional Clinical Hospital 1. Cox regression model was used to compare survival rate. By enrollment, females median age was 35 [25%-75%: 24 - 44] and in males median age was 34 [26 -42]. Median time duration from the first symptoms onset to the diagnosis verification was 3 [1-7] years in females and [1.5 - 8] years in males. The most common affected arteries were subclavian (55%), carotid (53%), and renal (42%). 5-year survival rate was 92%; 10-year survival rate was 90%; 15-year survival rate was 80%. The median term of survival was 34 [20 - 41] years. 31 deaths (18 males and 13 females) occurred during the follow-up period. Median age of death was 36 [32-44] in females, and 50 [40-57]) in males. The average disease course duration at the time of death was 9.25 years, median term being 6.5 [3-16] in females and 5 [3-10] in males. Also a total of 72 cardiovascular events were recorded during the follow-up period: 27 in men and 45 in women. The median duration of AT course by the development of the first ever event was 10 (5 -20). There were 24 cases of ischemic stroke, 3 transient ischemic attacks, 4 cases of hemorrhagic stroke. Median age of the first ever event was 38 (30 - 49.5). Time duration 4 years or more from AT symptoms onset to diagnosis was associated with significantly more frequent cardiovascular events (OR 1.8; 95% CI 1.07 – 3.34); and premature deaths (see table) by the 5th year of follow up (OR 2.9; 1.27- 6.55). In a retrospective cohort, time duration 4 years or more from TA symptoms onset to diagnosis verification was associated with higher risk of cardiovascular events and lower survival rate. [1]Mirouse C. et al. Ann. Rheum. Dis. 2018; 77(2): 10-48 [2]Dejaco C. et al. Ann. Rheum. Dis. 2018;77: 636-643 [3]Arend W.P. et al. Arthritis Rheum. 1990; 3(8): 1129-1134. Artem Popov Speakers bureau: Novartis, Menarini, AstraZeneca, Pfizer, Severnaya Zvezda, Romepharm, Irina Borodina: None declared, Lubov Shardina: None declared